Assessment of Surgical Complications With Respect to the Surgical Indication: Proposal for a Novel Index - Morand, Grégoire B.; Anderegg, Nanina; Kleinjung, Tobias; Bohlender, Jörg E.; Veraguth, Dorothe; Broglie, Martina A.; Holzmann, David; Huber, Alexander M.; Röösli, Christof; Soyka, Michael B. (Frontiers in Surgery, 2021)
Introduction: The Clavien-Dindo classification is a broadly accepted surgical complications classification system, grading complications by the extent of therapy necessary to resolve them. A drawback of the method is that is does not consider why the patient was operated primarily. Methods: We designed a novel index based on Clavien-Dindo but respecting the surgical indication. We surveyed an international panel of otolaryngologists who filled out a questionnaire with 32 real case inspired scenarios. Each case was graded for the surgical complication, surgical indication, and a subjective rating whether the complication was acceptable or not. Results: Seventy-seven otolaryngologists responded to the survey. Mean subjective rating and surgical complication grading for each scenario showed an inverse correlation (r2=0.147, p=0.044). When grading the surgical complication in respect of the surgical indication, the correlation with the subjective rating increased dramatically r2=0.307, p=0.0022)). Conclusion: We describe a novel index grading surgical complications respecting the surgical indication. In our survey, most respondents judged a complication as acceptable or not according to its grade but kept in mind the surgical indication. This subjective judgement could be quantified with our novel index.